B). Subtract 1.3 from both sides of the equation, subtract 4.6x to both sides of the equation, then divide by the coefficient of x.
C). Add 1.3 to both sides of the equation, subtract 4.6x to both sides of the equation, then divide by the coefficient of x.
D). Add 1.3 to both sides of the equation, subtract 4x to both sides of the equation, then divide by the coefficient of x.
The correct steps to solve the expression will be;
''Add 1.3 to both sides of the equation, subtract 4x to both sides of the equation, then divide by the coefficient of x.''
Option D is true.
What is an expression?
Mathematical expression is defined as the collection of the numbers variables and functions by using operations like addition, subtraction, multiplication, and division.
Given that;
The expression is,
⇒ -1.3 + 4.6x = 0.3 + 4x
Now,
Solve the expression as;
⇒ -1.3 + 4.6x = 0.3 + 4x
Add 1.3 both side, we get;
⇒ -1.3 + 4.6x + 1.3 = 0.3 + 4x + 1.3
⇒ 4.6x = 1.6 + 4x
Subtract 4x both side,
⇒ 4.6x - 4x = 1.6 + 4x - 4x
⇒ 0.6x = 1.6
Divide by 0.6,
⇒ x = 2.67
Thus, The correct steps to solve the expression will be;
''Add 1.3 to both sides of the equation, subtract 4x to both sides of the equation, then divide by the coefficient of x.''
Option D is true.
Learn more about the mathematical expression visit:
#SPJ5
Answer:
10 =x
Step-by-step explanation:
Let h(x) = -2x - 5. If h(x) = -25
-25 = -2x-5
Solve for x
Add 5 to each side.
-25+5 = -2x-5+5
-20 = -2x
Divide by -2
-20/-2 = -2x/-2
10 =x
Answer:
y=mx+c
We have to find the value of m and c.
Let's substitute the value of x and y from the table.
When x=1, y=15,
15= m(1)+c
m +c= 15 ------(1)
Now substitute another set of x and y values.
When x=2, y=24,
24= m(2)+c
2m +c= 24
c= 24 -2m ------(2)
Let me rewrite the two equations so that it is clearer for you to see.
m + c= 15 -----(1)
c = 24 -2m -----(2)
subst. (2) into (1):
m+ 24-2m= 15
-m= 15-24 (bring constants to 1 side, m terms to the other)
-m= -9 (simplify)
m= 9 ( divide by -1 throughout)
subst. m=9 into (2):
c= 24 -2(9)
c= 24-18
c= 6
Thus, the equation is y=9x+6.
When the cat is 3 years old, x=3.
When x=3,
y= 9(3)+6
y= 33.
Hence, the cat is 33 years old in human years.